a-amylase and a-glucosidase inhibitory effects of four piper species and GC-MS analysis of Piper crocatum (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hartini YS, Setyaningsih D. 2023. a-amylase and a-glucosidase inhibitory effects of four piper species and GC-MS analysis of Piper crocatum. Biodiversitas 24: 1313-1319. Antidiabetic activity can be determined by measuring the level of inhibition of a-amylase and/or a-glucosidase enzymes. Our previous study reported the activity of Piper crocatum as an inhibitor of a-amylase and a-glucosidase enzymes; hence, this study reported the same activity of three different piper species: Piper betle, Piper aduncum, and Piper retrofractum. It was also reported that the GC-MS chromatogram profile of P. crocatum. The Piper species was tested against a-amylase and a-glucosidase enzymes; activity measurements were carried out using UV-Vis spectrophotometry. Analysis of compound content in P. crocatum was carried out through GC-MS spectra and its library. The Piper species showed inhibitory activity against both a-amylase and a-glucosidase. Compared to P. betle, P. aduncum, and P. retrofractum, P. crocatum had the highest activity against both enzymes, with IC50 of 8,463 ± 0.318 mg/mL and 10,013 ± 0.070 mg/mL, respectively. The GC-MS profile of P. crocatum leaf methanol extract showed that there were 69 peaks, with the highest peak at RT 49,007 (20.49%), followed by RT 48,495 (11.00%), RT 6,984 (8.6%), RT 30.356 (4.51 %), RT 8,654 (3.44%), while the other peaks were below 3%. Based on the GC-MS dictionary, P. crocatum contains the main compounds: trans-isoelemicin/alpha-asarone, patchulane, myrcene, 1-octadecyne, and trans-ocimene. Therefore, Piper crocatum extract is considered to be developed as an antidiabetic agent.